Steel material

JP2025026370APending Publication Date: 2025-02-21NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024125632
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-08-01
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、強酸性および弱酸性の酸環境において優れた耐食性を有し、かつ、Ni含有量を低減した場合であっても耐脆化性に優れた鋼材が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026370000001
    Figure 2025026370000001
  • Figure 2025026370000002
    Figure 2025026370000002
Patent Text Reader

Abstract

To provide a steel material with superior corrosion resistance in both strong acid and weak acid conditions, demonstrating superior embrittlement resistance even with reduced Ni content.SOLUTION: A steel material comprises, in mass%, C: 0.01-0.10%, Si: 0.04-0.40%, Mn: 0.5-1.5%, Cu: 0.10-0.50%, Sb: 0.01-0.30%, Cr: 0.005-0.90%, Ni: 0.01-0.10%, Mo: 0.01-0.30%, Al: 0.005-0.050%, P: 0.020% or less, S: 0.015% or less, N: 0.0050% or less, O: 0.0005-0.0035%, and the balance: Fe and impurities, with 17.0≤(Cu / 64) / (S / 32)≤30.0, and (Sn / 119) / (Cu / 64)≤0.10.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel material. [Background technology]

[0002] Boiler furnaces and incinerators at waste incineration facilities generate exhaust gases that contain water vapor, sulfur oxides, hydrogen chloride, etc. When this exhaust gas is cooled in the exhaust gas chimney, etc., it condenses into sulfuric acid and hydrochloric acid, which causes severe corrosion of the steel materials that make up the exhaust gas passage, a phenomenon known as acid dew-point corrosion.

[0003] To address these problems, sulfuric acid dew-point corrosion resistant steels and highly corrosion resistant stainless steels have been proposed. For example, Patent Documents 1 to 5 propose steel materials with excellent sulfuric acid dew-point corrosion resistance to which Cu, Sb, Co, Cr, etc. have been added. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2001-164335 A [Patent Document 2] JP 2003-213367 A [Patent Document 3] JP 2007-239094 A [Patent Document 4] JP 2012-57221 A [Patent Document 5] International Publication No. 2021 / 095182 Summary of the Invention [Problem to be solved by the invention]

[0005] In an acid dew-point corrosion environment such as an exhaust gas chimney, when the temperature of the exhaust gas drops, the water vapor in the exhaust gas first condenses on the surface of the steel material, where sulfur oxides and hydrogen chloride dissolve. The high-concentration sulfuric acid and hydrochloric acid thus produced are highly reactive. Steel materials containing Cu, Sb, Cr, etc. have excellent corrosion resistance in such a strong acid environment.

[0006] On the other hand, in an environment of around 50°C, where the amount of water that condenses further increases, low concentrations of sulfuric acid and hydrochloric acid are produced. When the temperature of exhaust gas fluctuates in the environment in which steel is used, or when part of the steel is exposed to high-temperature exhaust gas and other parts are exposed to low-temperature exhaust gas, the steel is exposed to both strong and weak acid environments. Therefore, it is required to exhibit good corrosion resistance in both strong and weak acid environments. However, while conventional steels have excellent corrosion resistance in strong acid environments, there is still room for improvement in corrosion resistance in weak acid environments.

[0007] In addition, Cu has a large effect of improving corrosion resistance, but it is prone to segregation, and if it is contained alone, it may promote cracking after casting. In contrast, Ni has the effect of reducing the surface segregation of Cu. Therefore, in the past, in steel materials containing Cu, a certain amount or more of Ni has been contained according to the Cu content in order to ensure the embrittlement resistance of the steel material. However, since Ni is an expensive element, it is desirable to reduce the content of Ni.

[0008] The present invention aims to solve the above problems and provide a steel material that has excellent corrosion resistance in strong acid environments and weak acid environments, and also has excellent embrittlement resistance even when the Ni content is reduced. [Means for solving the problem]

[0009] The present invention has been made to solve the above problems, and the gist of the present invention is the following steel material.

[0010] (1) Chemical composition, in mass%, C: 0.01 to 0.10%, Si: 0.04 to 0.40%, Mn: 0.5-1.5%, Cu: 0.10-0.50%, Sb: 0.01 to 0.30%, Cr: 0.005~0.90%, Ni: 0.01 to 0.10%, Mo: 0.01 to 0.30%, Al: 0.005 to 0.050%, P: 0.020% or less, S: 0.015% or less, N: 0.0050% or less, O: 0.0005 to 0.0035%, The balance is Fe and impurities. The CI defined by the following formula (i) is 17.0 to 30.0, The following formula (ii) is satisfied: Steel material. CI = (Cu / 64) / (S / 32) (i) (Sn / 119) / (Cu / 64)≦0.10···(ii) In the above formula, the element symbols represent the contents (mass%) of the respective elements contained in the steel material.

[0011] (2) Chemical composition, in mass percent: C: 0.01 to 0.10%, Si: 0.04 to 0.40%, Mn: 0.5-1.5%, Cu: 0.10-0.50%, Sb: 0.01 to 0.30%, Cr: 0.005~0.90%, Ni: 0.01 to 0.10%, Mo: 0.01 to 0.30%, Al: 0.005 to 0.050%, P: 0.020% or less, S: 0.015% or less, N: 0.0050% or less, O: 0.0005 to 0.0035%, and further containing one or more selected from the group consisting of the following groups A, B, and C: The balance is Fe and impurities. The CI defined by the following formula (i) is 17.0 to 30.0, The following formula (ii) is satisfied: Steel material. CI = (Cu / 64) / (S / 32) (i) (Sn / 119) / (Cu / 64)≦0.10···(ii) In the above formula, the element symbols represent the contents (mass%) of the respective elements contained in the steel material. [Group A] One or more selected from the group consisting of Sn: 0.10% or less, As: 0.30% or less, Co: 0.30% or less, and W: 0.05% or less [Group B] One or more selected from the group consisting of Ti: 0.05% or less, Nb: 0.10% or less, V: 0.10% or less, Zr: 0.05% or less, Ta: 0.050% or less, and B: 0.010% or less [Group C] One or more selected from the group consisting of Ca: 0.010% or less, Mg: 0.010% or less, and REM: 0.010% or less

[0012] (3) The steel material according to (2) above, wherein the chemical composition contains one or more elements selected from Group A.

[0013] (4) The steel material according to (2) above, wherein the chemical composition contains one or more elements selected from the B group.

[0014] (5) The steel material according to (2) above, wherein the chemical composition contains one or more elements selected from the C group. Effect of the Invention

[0015] According to the present invention, it is possible to obtain a steel material which has excellent corrosion resistance in strong and weak acid environments, and which has excellent embrittlement resistance even when the Ni content is reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In order to achieve the above object, the present inventors have conducted detailed investigations into the corrosion resistance and embrittlement resistance of steel materials, and have come to the following findings.

[0017] The corrosion resistance in a strong acid environment is improved by including Cu, Sb, etc. in the steel material. However, as a result of further investigation by the present inventors, it was found that there is room for improvement in order to improve the corrosion resistance in a weak acid environment of pH about 0 to 2 while maintaining the corrosion resistance in a strong acid environment.

[0018] The present inventors conducted a detailed study on the effects of various steel materials containing different ratios of elements on corrosion resistance in strong acid environments and weak acid environments. As a result, it was found that by appropriately adjusting the Cu content relative to the S content so that it is not excessive, it is possible to maintain strong acid resistance while improving weak acid resistance by containing a certain amount or more of Cu relative to the S content. In other words, it was found that the balance of the Cu and S contents is important, and that by setting the value of the acid corrosion index CI=(Cu / 64) / (S / 32) to 17.0 to 30.0, it is possible to improve corrosion resistance in weak acid environments while maintaining corrosion resistance in strong acid environments.

[0019] By containing S and Cu within the above-mentioned range of CI, corrosion resistance in strong acid environments and weak acid environments can be ensured. However, as described above, in the present invention, Ni is reduced in order to reduce manufacturing costs. Therefore, the effect of improving embrittlement resistance by simultaneously containing a certain amount or more of Cu and Ni becomes insufficient.

[0020] Therefore, the present inventors further investigated a method for achieving both excellent corrosion resistance and excellent embrittlement resistance. As a result, it was found that when Ni is reduced, the embrittlement resistance is significantly deteriorated by simultaneously containing Sn and Cu. In other words, it was found that the desired embrittlement resistance can be obtained by reducing the Sn content relative to the Cu content even if Ni is reduced. Therefore, in the present invention, (Sn / 119) / (Cu / 64) is set to 0.10 or less.

[0021] In this way, excellent corrosion resistance in both strongly acidic and weakly acidic environments and excellent embrittlement resistance are obtained even with a reduced Ni content.

[0022] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.

[0023] (A) Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."

[0024] C: 0.01 to 0.10% C is an element that improves the strength of steel. However, if C is contained in excess, it deteriorates the weld heat affected zone. Therefore, the C content is set to 0.01 to 0.10%. The C content is preferably 0.03% or more. Moreover, the C content is preferably 0.08% or less, and more preferably 0.06% or less.

[0025] Silicon: 0.04 to 0.40% Silicon is an element that contributes to improving deoxidation and strength, and controls the morphology of oxides. However, when excessive silicon is contained, it reduces toughness. Therefore, the silicon content is set to 0.04 to 0.40%. The silicon content is preferably 0.10% or more, and more preferably 0.15% or more. The silicon content is preferably 0.35% or less, and more preferably 0.30% or less.

[0026] Mn: 0.5-1.5% Mn is an element that improves strength and toughness. However, if Mn is contained in excess, mechanical properties deteriorate. Therefore, the Mn content is set to 0.5 to 1.5%. The Mn content is preferably 0.8% or more, and more preferably 1.0% or more. Moreover, the Mn content is preferably 1.4% or less, more preferably 1.3% or less, and even more preferably 1.2% or less.

[0027] Cu: 0.10-0.50% Cu is an element that, when contained together with Sb, significantly exhibits corrosion resistance in a strong acid environment. However, when Cu is contained in excess, hot workability is reduced, impairing productivity. Therefore, the Cu content is set to 0.10 to 0.50%. The Cu content is preferably 0.15% or more, more preferably 0.20% or more, and even more preferably 0.25% or more. Moreover, the Cu content is preferably 0.45% or less, and more preferably 0.40% or less.

[0028] Sb: 0.01 to 0.30% Sb is an element that, when contained simultaneously with Cu, significantly exhibits corrosion resistance in a strong acid environment. However, when Sb is contained in excess, hot workability is reduced, impairing productivity. Therefore, the Sb content is set to 0.01 to 0.30%. The Sb content is preferably 0.05% or more, more preferably 0.10% or more, and even more preferably 0.15% or more. Moreover, the Sb content is preferably 0.25% or less, and more preferably 0.20% or less.

[0029] Cr: 0.005~0.90% Cr is an element that improves hardenability and strength. However, if Cr is contained in excess, it may deteriorate weldability and toughness. Therefore, the Cr content is set to 0.005 to 0.90%. The Cr content is preferably 0.80% or less, and more preferably 0.70% or less. In addition, the Cr content is preferably 0.01% or more, more preferably 0.03% or more, and even more preferably 0.05% or more.

[0030] Ni: 0.01 to 0.10% Ni has the effect of improving manufacturability in steel containing Cu. Cu has a large effect of improving corrosion resistance in a strong acid environment, but it is easily segregated, and if it is contained alone, it may promote cracking after casting. On the other hand, Ni has the effect of reducing the surface segregation of Cu. By containing Ni, the effect of suppressing the segregation of Cu and the cracking of the cast piece can be obtained. However, as described above, Ni is an expensive element, so its content is reduced in the present invention. Therefore, the Ni content is set to 0.01 to 0.10%. The Ni content is preferably 0.03% or more, more preferably 0.05% or more, and even more preferably 0.07% or more. Moreover, the Ni content is preferably 0.09% or less, and more preferably 0.08% or less.

[0031] Mo: 0.01 to 0.30% Mo is an element that improves corrosion resistance in a strong acid environment when contained simultaneously with Cu and Sb. However, since Mo is an expensive element, excessive content leads to a decrease in economic efficiency. Therefore, the Mo content is set to 0.01 to 0.30%. The Mo content is preferably 0.05% or more, and more preferably 0.10% or more. Moreover, the Mo content is preferably 0.25% or less, and more preferably 0.20% or less.

[0032] Al: 0.005 to 0.050% Al is added as a deoxidizer. However, if an excessive amount of Al is contained, it deteriorates the toughness of the weld metal part. Therefore, the Al content is set to 0.005 to 0.050%. The Al content is preferably 0.010% or more. Moreover, the Al content is preferably 0.040% or less, and more preferably 0.030% or less.

[0033] P:0.020% or less P is an impurity that reduces the mechanical properties and productivity of steel. Therefore, the upper limit of the P content is set to 0.020% or less. The P content is preferably 0.015% or less, and more preferably 0.010% or less. It is preferable to reduce the P content as much as possible, that is, the content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the P content may be 0.001% or more, or 0.003% or more.

[0034] S: 0.015% or less S is an impurity that reduces the mechanical properties and productivity of steel materials. Therefore, the upper limit of the S content is set to 0.015% or less. The S content is preferably 0.013% or less, and more preferably 0.010% or less. It is preferable to reduce the S content as much as possible, that is, the content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the S content may be 0.001% or more, or 0.003% or more.

[0035] N: 0.0050% or less N is an impurity that reduces the mechanical properties and productivity of steel materials. Therefore, an upper limit is set for the N content, making it 0.0050% or less. The N content is preferably 0.0045% or less, and more preferably 0.0040% or less. The N content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the N content may be 0.0010% or more. Furthermore, N has the effect of contributing to the improvement of mechanical properties, etc. by precipitating as fine nitrides. If this effect is desired, the N content may be 0.0020% or more.

[0036] O: 0.0005 to 0.0035% O is an element that has the effect of detoxifying MnS by bonding with MnS and preventing deterioration of corrosion resistance and mechanical properties in strong and weak acid environments. However, when O is contained in excess, it generates coarse oxides that become the starting point of corrosion in strong and weak acid environments. Therefore, the O content is set to 0.0005 to 0.0035%. The O content is preferably 0.0010% or more, and more preferably 0.0015% or more. In addition, the O content is preferably 0.0030% or less, and more preferably 0.0025% or less.

[0037] In the chemical composition of the steel material of the present invention, the balance is Fe and impurities. Here, the impurities refer to components that are mixed in due to raw materials such as ores and scraps or other factors during industrial production of the steel material, and are permissible within a range that does not adversely affect the steel material of the present invention.

[0038] CI = (Cu / 64) / (S / 32) (i) As described above, in order to improve the resistance to weak acid while maintaining the resistance to strong acid, it is necessary to control the Cu content relative to the S content. If the Cu content is too high relative to the S content, the corrosion resistance in a strong acid environment cannot be maintained. On the other hand, if the Cu content is too low relative to the S content, the corrosion resistance in a weak acid environment cannot be improved. Therefore, the value of CI defined in the above formula (i) is 17.0 to 30.0. The element symbols in the above formula (i) represent the content (mass%) of each element contained in the steel material.

[0039] Formula (i) is composed of the number of Cu and S atoms. That is, Cu / 64 and S / 32 are terms obtained by dividing the content of Cu and S by the mass number of each element, respectively. The value of formula (i) is preferably 20.0 or more, more preferably 23.0 or more. Also, the value of formula (i) is preferably 27.0 or less, more preferably 25.0 or less.

[0040] (Sn / 119) / (Cu / 64)≦0.10···(ii) As mentioned above, even if Ni is reduced, it is necessary to control the Sn content relative to the Cu content in order to ensure embrittlement resistance. If Ni is reduced and the Sn content becomes excessive relative to the Cu content, embrittlement resistance deteriorates. Therefore, the value of the left side of the above formula (ii) is set to 0.10 or less. The element symbols in the above formula (ii) represent the content (mass%) of each element contained in the steel material.

[0041] Formula (ii) is composed of the number of Sn and Cu atoms. That is, Sn / 119 and Cu / 64 are terms obtained by dividing the content of Sn and Cu by the mass number of each element, respectively. The value on the left side of formula (ii) is preferably 0.01 or more, more preferably 0.02 or more. Also, the value on the left side of formula (ii) is preferably 0.09 or less, more preferably 0.08 or less.

[0042] In the chemical composition of the steel of the present invention, one or more elements selected from Sn, As, Co, and W may be further contained within the ranges shown below in order to improve corrosion resistance in strong acid environments and weak acid environments. Note that these elements are not necessarily essential for steel materials, so the lower limit of the content is 0%. The reasons for limiting each element will be explained.

[0043] Sn: 0.10% or less Sn is an element that improves corrosion resistance in a strong acid environment, so it may be contained as necessary. However, if Sn is contained in excess, hot workability decreases. Therefore, the Sn content is set to 0.10% or less. The Sn content is preferably 0.09% or less, and more preferably 0.08% or less. In order to more reliably obtain the above effects, the Sn content is preferably 0.01% or more, and more preferably 0.03% or more.

[0044] As: 0.30% or less Although As does not have a significant effect compared to Sb, it is an element that is effective in improving corrosion resistance in strong acid environments and weak acid environments, so it may be contained as necessary. However, if As is contained in excess, toughness decreases. Therefore, the As content is set to 0.30% or less. The As content is preferably 0.25% or less, and more preferably 0.20% or less. In order to obtain the above effects more reliably, the As content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.04% or more.

[0045] Co:0.30% or less Co is an element that forms oxides to improve corrosion resistance in strong acid environments and weak acid environments, so it may be contained as necessary. However, if Co is contained in excess, economic efficiency decreases. Therefore, the Co content is set to 0.30% or less. The Co content is preferably 0.25% or less, and more preferably 0.20% or less. In order to more reliably obtain the above effects, the Co content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.05% or more.

[0046] W: 0.05% or less W is an element that improves corrosion resistance in strong acid environments and weak acid environments when contained simultaneously with Cu and Sb, so it may be contained as necessary. However, since W is an expensive element, excessive inclusion leads to a decrease in economic efficiency. Therefore, the W content is set to 0.05% or less. The W content is preferably 0.04% or less, and more preferably 0.03% or less. In order to obtain the above effects more reliably, the W content is preferably 0.01% or more, and more preferably 0.02% or more.

[0047] In the chemical composition of the steel of the present invention, in order to improve mechanical properties, etc., one or more elements selected from Ti, Nb, V, Zr, Ta, and B may be further contained within the ranges shown below. Note that these elements are not necessarily essential for steel materials, so the lower limit of the content is 0%. The reasons for limiting each element will be explained.

[0048] Ti: 0.05% or less Ti is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if Ti is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the Ti content is set to 0.05% or less. The Ti content is preferably 0.04% or less. In order to more reliably obtain the above effects, the Ti content is preferably 0.001% or more, and more preferably 0.005% or more.

[0049] Nb: 0.10% or less Nb is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if Nb is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the Nb content is set to 0.10% or less. The Nb content is preferably 0.09% or less, more preferably 0.08% or less, and even more preferably 0.07% or less. In order to obtain the above effects more reliably, the Nb content is preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.01% or more.

[0050] V:0.10% or less V, like Nb, is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if V is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the V content is set to 0.10% or less. The V content is preferably 0.08% or less, more preferably 0.06% or less, and even more preferably 0.04% or less. In order to obtain the above effects more reliably, the V content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more.

[0051] Zr: 0.05% or less Zr, like Ti, is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if Zr is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the Zr content is set to 0.05% or less. The Zr content is preferably 0.04% or less. In order to more reliably obtain the above effects, the Zr content is preferably 0.001% or more, and more preferably 0.005% or more.

[0052] Ta:0.050% or less Ta is an element that contributes to improving strength, and also contributes to improving corrosion resistance in strong acid environments and weak acid environments, although the mechanism is not necessarily clear, so it may be contained as necessary. However, Ta is an expensive element, and the inclusion of a large amount of Ta increases the steelmaking cost. Therefore, the Ta content is set to 0.050% or less. The Ta content is preferably 0.040% or less, more preferably 0.030% or less, and even more preferably 0.020% or less. In order to obtain the above effects more reliably, the Ta content is preferably 0.0010% or more, and more preferably 0.0050% or more.

[0053] B: 0.010% or less Since B is an element that improves hardenability and increases strength, it may be contained as necessary. However, even if B is contained in excess, the effect is saturated and the toughness of the base material and HAZ may decrease. Therefore, the B content is set to 0.010% or less. The B content is preferably 0.008% or less, more preferably 0.006% or less, and even more preferably 0.004% or less. In order to obtain the above effects more reliably, the B content is preferably 0.0003% or more, and more preferably 0.0005% or more.

[0054] In the chemical composition of the steel of the present invention, one or more elements selected from Ca, Mg and REM may be further contained within the ranges shown below for the purpose of deoxidization and inclusion control. Note that these elements are not necessarily essential in steel materials, so the lower limit of the content is 0%. The reasons for limiting each element will be explained.

[0055] Ca: 0.010% or less Ca may be added as necessary to form fine oxides. However, excessive addition of Ca leads to increased steelmaking costs. Therefore, the Ca content is set to 0.010% or less. The Ca content is preferably 0.008% or less, more preferably 0.006% or less, or 0.005% or less. In order to more reliably obtain the above effects, the Ca content is preferably 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more, or 0.0007% or more.

[0056] Mg: 0.010% or less Mg may be added as necessary to form fine oxides. However, excessive addition of Mg increases the steelmaking cost. Therefore, the Mg content is set to 0.010% or less. The Mg content is preferably 0.008% or less, and more preferably 0.005% or less. In order to more reliably obtain the above effects, the Mg content is preferably 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more.

[0057] REM: 0.010% or less REM (rare earth elements) are elements mainly used for deoxidization, and may be included as necessary to form fine oxides. However, excessive addition of REM leads to increased steelmaking costs. Therefore, the REM content is set to 0.010% or less. The REM content is preferably 0.0050% or less, and more preferably 0.0030% or less. In order to more reliably obtain the above effects, the REM content is preferably 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more.

[0058] Here, REM is a general term for Sc, Y, and lanthanoids, a total of 17 elements, and the REM content means the total amount of the above elements. Note that lanthanoids are industrially added in the form of misch metals.

[0059] (B) Anti-corrosion treatment The steel material of the present invention described above exhibits good corrosion resistance even when used as is. However, in order to further improve the corrosion resistance in strong acid environments and weak acid environments, the surface of the steel material may be coated with an acid-resistant paint, a heat-resistant paint, a heat-resistant and acid-resistant paint, or the like.

[0060] Examples of the anticorrosive coating made of an organic resin include resin coatings made of acid-resistant paints such as vinyl resins, epoxy resins, silicon resins, and phenol resins.

[0061] (C) Manufacturing method There is no particular restriction on the method for producing the steel material according to the present invention. For example, the steel material includes a steel plate, a steel pipe, etc., which are produced by hot rolling an ingot having the above-mentioned chemical composition, and further cold rolling it as necessary. There is no particular restriction on the heating conditions when performing the hot rolling, and normal conditions may be adopted.

[0062] When manufacturing steel materials, steel is melted in a conventional manner, and after adjusting the components, the steel slab obtained by casting is hot-rolled and, if necessary, cold-rolled to manufacture the steel material. After hot rolling, the steel may be water-cooled as it is, or air-cooled, and then reheated and quenched. After hot rolling, the steel may be wound into a coil. After hot rolling, the steel may be cold-rolled and then further heat-treated.

[0063] When manufacturing steel pipes, steel plates may be formed into a tubular shape and welded, and electric resistance welded steel pipes, forged welded steel pipes, spiral steel pipes, etc. Seamless steel pipes manufactured by hot extrusion or piercing rolling of steel billets are also included in the steel materials of the present invention.

[0064] The treatment for covering with the above-mentioned anticorrosive coating may be carried out by a normal method. Also, it is not necessarily required to apply an anticorrosive coating to the entire surface of the steel material, and it is sufficient to perform anticorrosive treatment only on one side of the steel material that is exposed to a corrosive environment, or only on the outer or inner surface in the case of a steel pipe, that is, only on at least a part of the steel material surface.

[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES

[0066] Steel having the chemical composition shown in Table 1 was melted and formed into a 50 kg ingot, which was then hot forged in a normal manner to produce a block with a thickness of 60 mm. The block was then heated at 1120°C for 1 hour, hot rolled, and finished at 850°C to a thickness of 20 mm, and then cooled to room temperature in the air to produce a steel plate. Note that the "-" in the left-hand side value column of formula (ii) in Table 1 means that no calculation was performed because Sn was not contained.

[0067] [Table 1]

[0068] <Corrosion resistance> Two test pieces measuring 3 mm in thickness, 25 mm in width, and 25 mm in length were taken from the center of each steel plate, and each was finished with wet #600 polishing to prepare test pieces for corrosion resistance evaluation. One of the test pieces was subjected to a hydrochloric acid immersion test in which it was immersed in a 3% HCl aqueous solution at 55°C for six hours to simulate a strong acid environment. The remaining test piece was subjected to a hydrochloric acid immersion test in which it was immersed in a 0.14% HCl aqueous solution at 65°C for six hours to simulate a weak acid environment.

[0069] Then, the corrosion rate was calculated from the corrosion weight loss of the test piece in the hydrochloric acid immersion test. In this example, the corrosion rate in a 3% HCl aqueous solution at 55°C was 1.5 mg / cm 2 / h or less, and the corrosion rate in a 0.14% HCl solution at 65°C is 5.0 mg / cm 2 / h or less, it was determined that the corrosion resistance was excellent.

[0070] <Embrittlement resistance> The surface of the hot-rolled material rolled under the above conditions was visually inspected for appearance, and embrittlement resistance was evaluated by rating cracks as "X" and no cracks as "O."

[0071] Table 2 shows the results of the hydrochloric acid immersion test and the evaluation of embrittlement resistance. Note that "-" in Table 2 means that test pieces could not be taken due to deterioration of embrittlement resistance, and therefore corrosion resistance could not be evaluated. "Corrosion rate (condition 1)" in Table 2 shows the corrosion rate in a 3% HCl aqueous solution at 55°C, and "Corrosion rate (condition 2)" shows the corrosion rate in a 0.14% HCl aqueous solution at 65°C.

[0072] [Table 2]

[0073] As shown in Table 2, Test Nos. 1 to 19 and 23 to 30, which satisfy all the provisions of the present invention, were excellent in both corrosion resistance and embrittlement resistance. In contrast, Test Nos. 20 to 22, which are comparative examples, were inferior in corrosion resistance or embrittlement resistance. [Industrial Applicability]

[0074] The steel material of the present invention can be used in smoke exhaust systems for boilers that burn fossil fuels such as heavy oil and coal, gas fuels such as liquefied natural gas, general waste such as urban waste, industrial waste such as waste oil, plastics, and exhaust tires, and sewage sludge, etc. Specifically, it can be suitably used for flue ducts, casings, and heat exchangers of smoke exhaust systems, gas-gas heaters consisting of two heat exchangers (a heat recovery unit and a reheater), desulfurization equipment, electric dust collectors, induced draft fans, basket materials and heat transfer element plates of rotary regenerative air preheaters, etc.

Claims

1. The chemical composition, in mass%, is C: 0.01 to 0.10%, Si: 0.04-0.40%, Mn: 0.5-1.5%, Cu: 0.10-0.50%, Sb: 0.01 to 0.30%, Cr: 0.005-0.90%, Ni: 0.01 to 0.10%, Mo: 0.01-0.30%, Al: 0.005-0.050%, P: 0.020% or less, S: 0.015% or less, N: 0.0050% or less, O: 0.0005-0.0035%, The balance is Fe and impurities. The CI defined by the following formula (i) is 17.0 to 30.0, The following formula (ii) is satisfied: Steel material. CI=(Cu / 64) / (S / 32)...(i) (Sn / 119) / (Cu / 64)≦0.10...(ii) In the above formula, the element symbols represent the contents (mass%) of the respective elements contained in the steel material.

2. The chemical composition, in mass%, is C: 0.01 to 0.10%, Si: 0.04-0.40%, Mn: 0.5-1.5%, Cu: 0.10-0.50%, Sb: 0.01 to 0.30%, Cr: 0.005-0.90%, Ni: 0.01 to 0.10%, Mo: 0.01-0.30%, Al: 0.005-0.050%, P: 0.020% or less, S: 0.015% or less, N: 0.0050% or less, O: 0.0005-0.0035%, and further containing one or more selected from the group consisting of the following groups A, B, and C: The balance is Fe and impurities. The CI defined by the following formula (i) is 17.0 to 30.0, The following formula (ii) is satisfied: Steel material. CI=(Cu / 64) / (S / 32)...(i) (Sn / 119) / (Cu / 64)≦0.10...(ii) In the above formula, the element symbols represent the contents (mass%) of the respective elements contained in the steel material. [Group A] One or more selected from the group consisting of Sn: 0.10% or less, As: 0.30% or less, Co: 0.30% or less, and W: 0.05% or less [Group B] One or more selected from the group consisting of Ti: 0.05% or less, Nb: 0.10% or less, V: 0.10% or less, Zr: 0.05% or less, Ta: 0.050% or less, and B: 0.010% or less [Group C] One or more selected from the group consisting of Ca: 0.010% or less, Mg: 0.010% or less, and REM: 0.010% or less

3. The steel material according to claim 2 , wherein the chemical composition contains one or more elements selected from the group A.

4. The steel material according to claim 2 , wherein the chemical composition contains one or more elements selected from the B group.

5. The steel material according to claim 2 , wherein the chemical composition contains one or more elements selected from the C group.

Citation Information

Patent Citations

  • High workability and good weldability sulfuric acid dew point corrosion resistant steel sheet

    JP2001164335A

  • Low alloy steel having excellent hydrochloric acid- corrosion and sulfuric acid-corrosion resistance and welded joint thereof

    JP2003213367A

  • Acid corrosion resistant steel

    JP2007239094A

  • Acid dew-point corrosion resistant steel and exhausted gas flow path structure member

    JP2012057221A

  • Steel material

    WO2021095182A1